NOSTALGIA IN JOHN CHEEVER’S THE HOUSEBREAKER OF SHADY HILL AND OTHER STORIES (Journal of Contemporary Philology, 2023)
The paper deals with the notion and function of nostalgia in John Cheever’s short story cycle The Housebreaker of Shady Hill and Other Stories (1958). The analysis relies on Svetlana Boym’s definition of nostalgia as “a longing for a home that no longer exists or has never existed” (2001: xiii) and on Jennifer Smith’s (2017) study of nostalgia in the American short story cycle. The objective is to examine how and for what purposes Cheever’s cycle employs nostalgia in individual stories, and to show whether different evocations of nostalgia present partial or false versions of the past. Having in mind the recursive and accretive nature of the cycle as a genre, the authors intend to examine how individual stories come together to render a more collective sense of nostalgia, whether coherent or ambivalent, that might be in a correlation with a specific middle-class suburban locality of the American Northeast.
Keywords: nostalgia; John Cheever; the short story cycle; American literature; The Housebreaker of Shady Hill and Other Stories